The Role of Images in the Structure of Poetic Works - Norova Mekhri Bakhtiyorovna (Researchparks Publishing, 2022)
In English, tropes can be both auxiliary and core in a poetic landscape. In the first case, tropes are explicit images of referents used to describe their denotations. The correct meanings of such tropes are extinguished, just like the deleted, “etymological” tropes, and the semantic features that do not contradict the characteristic image of the referent come to the fore. The article describes the lexical expression of the poetic image in English literature